The Genealogy and Theology of Isaiah 11:1 - Sumner, Stephen T. (Vetus Testamentum, 2018)
Isaiah 11:1 traces the genealogy of ideal king back to Jesse and not a Davidic king in order to portray him as a new, or second, David. This depiction was motivated by the religious decline of the Davidides, and it allowed for a sense of disjuncture, or distance, from the Davidic line in order to claim royal legitimacy on theological grounds.